A dictionary of early Middle Turkic - Boeschoten, Hendrik. (Leiden ; Boston)
xi, 596 sayfa
Keywords: “In A Dictionary of Early Middle Turkic Hendrik Boeschoten describes the lexical material contained in works written in different varieties of Eastern Turkic in and around the fourteenth century, e.g. before the classical age of Chaghatay Turkic; late Karakhanid, Khwarezmian Turkic, Golden Horde Turkic, Mamluk Turkic, and early Azeri. As the existing, previously published dictionaries are now antiquated and hardly cover this period (most relevant works were not yet known at their time of writing), A Dictionary of Early Middle Turkic is a most welcome addition to the field“ --